Species identification of stranded seaweeds on eastern seashores of Thailand and utilization as a sole carbon source for single cell oils synthesized by oleaginous yeasts (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Chantarasiri A. 2020. Species identification of stranded seaweeds on eastern seashores of Thailand and utilization as a sole carbon source for single-cell oils synthesized by oleaginous yeasts. Biodiversitas 21: 2353-2361. Many stranded seaweeds are left to decompose on the seashore. This study aimed to identify and utilize the stranded seaweeds collected from seashores in Rayong Province on the east coast of Thailand. Seaweeds were identified as Dictyota dichotoma strain A and Padina australis strain B based on their distinctive morphology and 18S rDNA sequence analyses. The most abundant seaweed, D. dichotoma strain A, was analyzed for chemical compositions following AOAC standard methods. This seaweed was considered a low-cost carbon source for the cultivation of three oleaginous yeasts without any other nutrient supplements. All oleaginous yeasts utilized the carbon source from Dictyota medium for growth and accumulation of single-cell oils (SCOs). The oleaginous yeast, Cryptococcus albidus strain TISTR 5103 accumulated SCOs at 51% (w/w). The resulting SCOs from oleaginous yeasts comprise many fatty acids with 10 to 22 carbon atoms. This study is the first to identify stranded seaweeds in Rayong Province using morphological and genetic techniques. Results showed the potential application of stranded seaweeds as a low-cost carbon source for SCO biosynthesis of oleaginous yeasts.
Keywords: Cryptococcus albidus; Dictyota dichotoma; oleaginous yeast; seaweed; single cell oil